The test-retest reliability and spatial tuning of serial dependence in orientation perception - Kondo, Aki; Murai, Yuki; Whitney, David (Journal of vision (Charlottesville, Va.), 2022)
Humans perceive objects and scenes consistently, even in situations where visual input is noisy and unstable. One of the mechanisms that underlies this perceptual stability is serial dependence, whereby the perception of objects or features at any given moment is pulled toward what was previously seen. Although recent findings from several studies have reported large individual differences in serial dependence, it is not clear how stable the serial dependence is within an individual. Here, we investigated the stability of serial dependence in orientation perception over two different days within the same observers. In addition, we also examined the visual field location specificity of perceptual serial dependence. On each trial, observers viewed a Gabor patch and then reported its apparent orientation by adjusting the orientation of a bar. For each observer, the Gabor was located in the foveal or peripheral (10° right or left eccentricity) visual field on both days or changed location from day to day. The results showed a very high degree of test-retest reliability in serial dependence measured across days within individual observers. Interestingly, this high within-subject consistency was only found when serial dependence was measured at the same visual field location. These results suggest that individual differences in serial dependence are stable across days, and that the spatiotemporal range in which the previous stimulus assimilates the perception of the current stimulus (the continuity field) may vary across different visual field locations in an observer-specific manner.